A matter of attachment? How adoptive parents foster post-institutionalized children's social and emotional adjustment - Barone, Lavinia; Lionetti, Francesca; Green, Jonathan (Attachment & human development, 2017)
The current study investigates the contribution of children's age at adoption (M = 46.52 months, SD = 11.52 months) and parents' attachment on post-institutionalized children's attachment and social-emotional adjustment. A total of 132 subjects, 48 post-institutionalized children aged 3-5 years, and their adoptive parents, took part in the study. One year from adoption, children's attachment distribution was as follows: 31% secure, 42% disorganized, and 27% insecure. Parents' secure attachment increased children's probability of presenting a secure attachment pattern; specifically, mothers' attachment patterns were most strongly associated with those of their adopted children, with fathers' making an additional contribution. Two years from adoption, secure children showed more adequate social competences than their insecure and disorganized peers and presented better emotional comprehension. The effect of age at adoption was delimited to a marginal association with behavioral problems. This pattern of associations suggests that attachment - both of adoptive parents and of children - substantially fosters social-emotional adjustment of post-institutionalized children who have experienced a period in emotionally neglecting environments beyond their first year of life, regardless of their age at adoption. Implications for policies and practices are discussed.